Clinical outcomes of vaginectomy and laser ablation for the treatment of post-hysterectomy women with vaginal high-grade squamous intraepithelial lesions: A retrospective study. (May 2020) - Shen, Fang; Sun, Shu-gen; Zhang, Xu-yin; Wang, Qing; Ding, Jing-xin; Hua, Ke-qin
Abstract: Objective: To evaluate the clinical outcomes of vaginectomy and laser ablation for the treatment of vaginal high-grade squamous intraepithelial lesion (HSIL) patients who underwent previous hysterectomy for cervical HSIL or cancer. Study Design: The clinicopathologic data and follow-up information of 167 post-hysterectomy vaginal HSIL patients who underwent laser ablation or vaginectomy were retrospectively reviewed from 2010 to 2018 at the Obstetrics and Gynecology Hospital of Fudan University. Results: Of the 167 vaginal HSIL patients enrolled, 74 patients underwent vaginectomy, and 93 patients underwent laser ablation. At a median follow-up of 15 months, 13 (7.8 %) patients experienced progression to vaginal cancer, and 22 (13.2 %) patients had persistent/recurrent disease. Upon multivariate analysis, laser ablation (OR: 5.16, p = 0.02), cytology indicating HSIL (OR: 25.45, p = 0.00), and a shorter interval between previous hysterectomy and vaginal HSIL diagnosis (< 24 vs ≥ 24 months, OR: 0.10, p = 0.02) were associated with disease persistence/recurrence. In post-hysterectomy for cervical HSIL patients, the vaginectomy group had a significantly higher recurrence-free survival rate (RFS, 94.5 % vs 69.0 %, p = 0.00) and a similar progression-free survival rate (PFS, 96.4 % vs 91.4 %, p = 0.17) compared with the laser ablation group. Among post-hysterectomy for cervical cancer patients, RFS (89.5 % vs 65.7 %, p = 0.04) and PFS (100.0 % vs 82.9 %, p = 0.05) were both higher in the vaginectomy group than in the laser ablation group. Conclusion: Compared with laser ablation, vaginectomy resulted in better clinical outcomes among vaginal HSIL patients who had undergone previous hysterectomy for cervical neoplasia.